Construct validity and reliability of malaysian academician happiness index: A rasch model approach for pilot study - Khairunesa Isa; Wan Hanim Nadrah Wan Muda; Laily Paim; Khadijah Alavi; Jalihah Md Shah; Nor Aisah Jamil (2020)
This study was conducted to generate empirical evidence on validity and reliability of the items of Malaysian Academician Happiness Index (MAHI) using Rasch Model by Winstep software version 3.69.1.11. The construct validity was examined by analysing the point-measure correlation index (PTMEA), infit and outfit MNSQ values;. A survey technique was used as the major method on the MAHI instrument on 30 academicians at one of the Malaysian public university. The result showed that the reliability of MAHI instrument item was 0.72. Statistical data obtained showed that out of 50 items, 5 items or 6% of the instrument were suggested to be omitted. This study is hoped to bring a new holistic dimension on academician happiness measurement index that can help the academicians to have more resilience towards the educational world.